Challenging lesbian morms: Intersex, transgender, intersectional and queer perspectives. - Pattatucci-Aragon, Angela (Taylor and Francis, 2013)
What constitutes lesbian identity? The term homonormativity describes current prevailing idealized assumptions about lesbian identity. This concept, however, marginalizes subgroups within the greater lesbian population. Challenging Lesbian Norms: Intersex, Transgender, Intersectional, and Queer Perspectives dynamically confronts homonormativity in lesbian communities by presenting expert multidisciplinary discussion about what is a definable lesbian identity. This text sensitively explores difficult issues about gender policing and the viewpoints in lesbian communities that hold that transgender, intersectional, and queer individuals are considered to have 'false consciousness.' Consequences of lesbian normativity, both for lesbian communities and for marginalized groups are examined through literary criticism, lesbian, feminist, and queer theories, corporeal philosophy, film, television, cultural criticism, personal narratives, public health, and field research. The issue of the authenticity of lesbian identity causes rifts between some lesbian communities and the groups that strive to be included, yet are still marginalized. Challenging Lesbian Norms directly exposes practices and beliefs within lesbian communities that lead to the assumption of the prototypical lesbian. The book courageously reveals the similarities of lesbian normative stances with other views such as Christian conservative rhetoric, and reviews the health consequences of being marginalized within the lesbian communities. This text actively challenges the foundational notion within lesbian communities that a stable, immutable lesbian sex exists.
https://transreads.org/wp-content/uploads/2021/07/2021-07-23_60fa0c6d271e3_ChallengingLesbianNormsIntersexTransgenderIntersectionalandQueerPerspectivesbyAngelaPattatuchiz-lib.org_.pdf
Keywords: approches et analyses; corps; genre; identités LGBTQIA2+; lesbianisme; personnes lesbiennes; personnes trans*; ressource en ligne; santé; sexualité; thématiques; violences